The Carbothermal reduction of fayalite: thermodynamic and non-isothermal kinetic analysis - Li, Zhi; Ma, Guojun; Zou, Jingjing; Zheng, Dingli; Zhang, Xiang (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
The present paper investigated the thermodynamics and kinetics of carbothermal reduction of fayalite by non-isothermal method combining with thermogravimetric analyzer and applying the Flynn-Wall-Ozawa (FWO) and Málek models. According to the thermodynamic analysis, the starting temperature of direct reduction reaction of fayalite is 806.79℃ in the standard state. The indirect reduction reaction can not take place in the standard state. While the volume percentage of CO is higher than 86 vol.% in nonstandard state, the indirect reduction can take place in the range of experimental temperature. Meanwhile, Boudouard reaction can promote the indirect reduction process. The kinetic analysis results show that at the temperature below 1100℃, the main reduction reaction is the direct reduction between fayalite and graphite. With the temperature increasing, the fayalite reacts with CO generated from the gasification of graphite. The activation energy of carbothermal reduction of fayalite increases with the increase of reduction rate firstly and then decreases when the reduction rate is larger than 50%. The average activation energy is 524.41 kJ/mol. The carbothermal reduction of fayalite is multistep reaction. The controlling step in the initial stage is the gasification of graphite. As the reaction proceeding, the generated CO provides a good kinetics condition for the carbothermal reduction of fayalite, and the controlling step of the reaction is the nucleation and growth of the metallic iron.
Keywords: Fayalite; Non-isothermal kinetics; Carbothermal reduction; Activation energy